Experiments in partially balanced incomplete block design with some common treatments added to each block - Oliveira, Antonio Carlos de (Pesquisa Agropecuaria Brasileira, 2014)
Intrablock analysis and analysis with recovery of inter-block information are considered for the case in which experiments are designed in partially balanced incomplete block design (PBIB), but some common treatments are added to each block. Formulas for sums of squares in the analysis of variance, the adjusted treatment means and variances of treatment differences were obtained. An example is given for illustration